Political Consumerism and Producerism inTimes of Crisis. A Social Movement Perspective? - Andretta, Massimiliano; Guidi, Riccardo (PARTECIPAZIONE E CONFLITTO, 2017)
Local alternative consumerism practices supported by organized citizens seem to provide the only way to save small agro producers from economic failure. At the same time, organized small producers provide incentives to new forms of co-production. By relying on semi-structured and in depth interviews, a focus group, document analysis and participant observation, in this article, we show how Tuscan Solidarity Purchase Groups, together with producers, act in the context of the economic crisis, and how the crisis has influenced them. First, we show how organized political consumers and small producers are intensifying their relations to overcome the threats of the crisis. Secondly, we illustrate how these consumer-producer relations concretize in a co-production experience. Our case study shows that, in the adverse context of the economic crisis, local alternative consumerism practices can develop alternative processes through civic food networks and (re)discover radical forms of food democracy. That is they build a local Sustainable Community Movement.